MANAJEMEN CLUB ATLETIK LOKOMOTIF KOTA SALATIGA TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study is to describe the management of Club Athletic Locomotive Salatiga 2013. This study used a qualitative descriptive approach, data collection techniques performed using interviews, observation, and documentation. Analysis of the data in this study is a qualitative descriptive method of collecting data, sorting the data, study the data, describe the data and make the final analysis. Research results Athletic Club Management locomotive is quite good, for sports management components such as athletes and coaches at the Club Athletic locomotive Salatiga say well, for coaches and administrators can not be said to be good because the board locomotive most of the children so that the performance of the board chairman is not maximum. In the medium and prasaranana good enough, for the funding can not be said to be good because now PT KAI in providing funds slightly decreased because the locomotive achievement, good exercise program, and sports performance can not be said to be good because of the achievements of locomotives declined since abandoned by athletes flagship. Concluded that the management of Club Athletic locomotive in 2013 can not be said to be good.